Kestabilan Model Mangsa Pemangsa dengan fungsi respon Holling tipe IV dan penyakit pada pemangsa - A. Muh. Amil Siddik; Syamsuddin Toaha; Andi Muhammad Anwar (Jurnal Matematika, Statistika dan Komputasi, 2021)
Stability of equilibrium points of the prey-predator model with diseases that spreads in predators where the predation function follows the simplified Holling type IV functional response are investigated. To find out the local stability of the equilibrium point of the model, the system is then linearized around the equilibrium point using the Jacobian matrix method, and stability of the equilibrium point is determined via the eigenvalues method. There exists three non-negative equilibrium points, except , that may exist and stable. Simulation results show that with the variation of several parameter values infection rate of disease , the diseases in the system may become endemic, or may become free from endemic.